Spinal Dysraphism: Presentation, Management and Outcome of Patients undergoing Surgery - Gupta, Dr. Vipul Kumar; Bhat, Dr. Ankur; Sharma, Shilpi; Gupta , Dr. Bhumika (International Journal of Innovative Research in Medical Science, 2021)
The development of the spinal cord can be summed up in three developmental stages: gastrulation (2–3 weeks), primary neurulation (3-4 weeks) and secondary neurulation (5–6 weeks). Any sort of deviance in any of these stages causes anomalies in spine and spinal cord; these anomalies are referred as spinal dysraphism. The approximated incidence of spinal dysraphism is about 1/1000 live births. The present study aims at varied presentations, management and surgical consequences in spinal dysraphism. Methods: A study on surgical treatment of spinal dysraphism was done over the period of 6 months from December 2019- May 2020 at GMC, Jammu. In the study at hand; the clinical aspects, management and surgical outcomes in case of spinal dysraphism were characterized. Results: A total of 30 patients of spinal dysraphism were operated with 70% males and 30% females. The age group selected for the study was between 0-3 years. In early post-operative period the most common symptoms were found to be meningitis (6%), minor wound infection (10%), major wound infections (14%) and 14% patients reported CSF leakage. Out of 30 patients who underwent surgery, 67% patients had good outcome, 20% reported satisfactory outcome and 13% reported poor outcome with an overall mortality rate of 13%. Conclusion: Spinal dysraphism is a complex disorder and requires a multidisciplinary approach for management. The present study suggests that surgery is the prominent treatment along with good post-operative care for the better life of the patient.